(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
In order to study the history of women “Self-writtings” are a very important source since they provide private information about their authors. Thanks to these sources/writings one can get closer to the experiences and reflections of their female writers. Besides, one can also study the tautness between the gender rules established in a specific historical moment and women’s initiatives regarding those rules. This article is aimed at contributing to the study of the Spanish civil war from a gender perspective, with the analysis of Mi Guerra de España, the memories of Mika Etchebéhère, an argentine militiawoman. This is a particular useful case that shows the reorganization of the relationships between genders during that historical period.